Towards a more scientific way of studying multicultural management - R. Rijamampianina; T. Maxwell (South African Journal of Business Management, 2002)
In recent years, the management of cultural diversity has become a popular topic within management in general and organisational behaviour and human resource management in particular. The progressive movement of the world into the post-modern era calls for a comprehensive, practical and realistic strategy to change not only the demographics of organisational members and their attitudes, but also the way in which multicultural organisations are managed. Controversies and uncertainties regarding current outcomes still prevail, possibly because of a lack of application of more scientific management styles and methodologies. Management approaches often appear to be based on unfounded assumptions, superficial observations and simplistic assessments. As a result, the derived outcomes are incongruent, oversimplistic, unrealistic and unreliable. To ensure the success of organisations in the growing global market, managers need to establish an effective approach to managing cultural diversity. This article examines some of the traditional concepts of culture and cultural diversity and employs illustrative empirical data to suggest a more scientific approach to the measurement of cultural diversity and its impact on the work environment and management.
Keywords: 650